PANMUSICALITY OF O. OLES’S DRAMATURGY - Oleksiuk, H. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article brings up problems of music elements functioning in symbolic-and-lyrical dramaturgy of O. Oles. In particular, the attention is drawn to the fact how skillfully the Ukrainian playwright uses music rhythm with the purpose of rhythmization of a drama spectacle, how with the help of an imaginary sounding of a melody the characteristics of his characters is amplified, dramatic remarques are poetized etc.. Therefore, it was proved, that a lot of dramatic works of the writer, in which such type of the author’s ideological-and-aesthetic consciousness as symbolism is present, may be considered as a phenomenon of music order, in which oral and dramatic-music arts are intrinsically connected.